2020
DOI: 10.1080/10799893.2020.1805628
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of plant-derived phytochemicals as anti-cancer agents targeting cyclin dependent kinase-2, human topoisomerase IIa and vascular endothelial growth factor receptor-2

Abstract: Cancer is caused by a variety of pathways, involving numerous types of enzymes, among them three enzymes: Cyclin dependent kinase-2 (CDK-2), Human topoisomerase IIα and Vascular Endothelial Growth Factor Receptor-2 (VEGFR-2) are three most common enzymes that are involved in the cancer development. Although many chemical drugs are available in the market, plant sources are known to contain a wide variety of agents that are known to possess anticancer activity. In this experiment, total thirty compounds were an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 123 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…All of the 4 ligands were predicted to have significant gap energy representing their possibility to undergo a chemical reaction. However, among the four best selected ligands, coptisine, with its lowest gap energy, was predicted to have higher probability to undergo a chemical reaction [25,117] (Table 9 and Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the 4 ligands were predicted to have significant gap energy representing their possibility to undergo a chemical reaction. However, among the four best selected ligands, coptisine, with its lowest gap energy, was predicted to have higher probability to undergo a chemical reaction [25,117] (Table 9 and Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…By simulating the interaction between ligand and receptor in the computer software, the docking system assigns scoring functions to the bound ligands which reflect their binding affinity. The lower docking score represents the greater binding affinity and vice-versa [24,25]. The current study was designed to predict the best ligands among 50 selected phytochemicals with potential anti-AChE activities based on the molecular docking analysis (Table 2).…”
Section: The Cholinergic Hypothesis and The Development Of Alzheimer'mentioning
confidence: 99%
“…XP G Score is generated in the IFD experiment, which is an empirical scoring function that estimates the ligand binding free energy. The lowest value of XP G Score is considered as the best value and is always appreciable [71, 72, 73, 74] . In the MM-GBSA study, based on the ΔG Bind score, XP G Score value and IFD score, coptisine can be considered as the best ligand molecule among the selected three ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the roles growth factor receptors play in the development and progression of cancer, it is necessary to develop suitable drug candidates that can effectively inhibit growth factors at the sites of receptors with little or no effects. Binding a nity between ligands and receptors is determined by the binding energy, the lower the energy the higher the binding a nity [9]. For this purpose, 50 bioactive compounds were screened against ERRB2/HER2, ERRB3/HER3, VEGFR-2, VEGFR-3 and FGFR-2.…”
Section: Docking Analysismentioning
confidence: 99%
“…In some cancer, these receptors are often overexpressed leading to uncontrolled proliferation and differentiation, [8] their ampli cation activates both inherent and acquired resistance to cancer treatments. Overexpression of HER-2 gene were found in breast, bladder, lung and glial carcinomas, HER-3 gene in aggressive metastatic breast, ovarian, lung, gastric, invasive urothelial bladder and endometrial carcinomas, VEGFR1-3genes found in large number of tumors like bladder, colon, breast, lung, brain, prostate, gastric, kidney, thyroid and ovarian cancer cells, FGFR-2 gene in gastric, breast, endometrial and lung carcinomas [6,9]. The role of these receptors in cancer progression has made them a necessary therapeutic target for effective cancer therapy.…”
Section: Introductionmentioning
confidence: 99%